Соціально-комунікаційна функція міфу в прадавньому суспільстві у світлі міфологічної концепції О.О. Потебні - Казакова, Т.В. (Харківський національний університет імені В. Н. Каразіна, 2007)
Исходя из толкования А. А. Потебней мифа как отражения и объяснения окружающей действительности той или иной человеческой группой, автор статьи рассматривает миф как наиважнейшую составляющую (наряду с ритуалом) социально-массовой коммуникации первобытного общества. Reasoning from the basis of Potebnia’s interpreting the myth as a reflection and from any specific human group’s explaining the surrounding reality, the author approaches the myth as a most important component (alongside the ritual) of the social mass communication in a primitive society.
Keywords: Потебня; міф; міфологічна концепція